Lipid and protein oxidation in charqui meat and jerked beef - Marta A. A. Souza; Jesui V. Visentainer; Rafael H. Carvalho; Fabianne Garcia; Elza I. Ida; Massami Shimokomaki (Brazilian Archives of Biology and Technology, 2013)
In this study, the changes in the lipid (Lox) and protein oxidation (Pox) were measured quantitatively by TBARS and carbonyl methods, respectively, throughout the salting and drying steps of charqui meat (CH) and jerked beef (JB) preparation and their storage up to 60 days. The experiment was carried out on CH samples treated with brine (20.0%) and JB with same brine solution added with sodium nitrite (0.02%). After 60 days of storage, the carbonyl substances in CH were 2.77nmol mg-1 while in the JB samples, there was 61.0% oxidation inhibition. The TBARS determination revealed a Lox inhibition by approximately 5-fold in the latter samples. These results indicated that in the metmyoglobin molecule, the nitrite kept the Fe in the Fe2+ state in JB samples whereas in CH, the Fe was oxidized to Fe3+, which catalyzed the oxidation reactions more efficiently, leading to the higher development of Lox and Pox.